Cognitive Predictors of Work Among Social Security Disability Insurance Beneficiaries With Psychiatric Disorders Enrolled in IPS Supported Employment. (31st August 2017) - McGurk, Susan R; Drake, Robert E; Xie, Haiyi; Riley, Jarnee; Milfort, Roline; Hale, Thomas W; Frey, William
Abstract: Background: Impaired cognitive functioning is a significant predictor of work dysfunction in schizophrenia. Less is known, however about relationships of cognition and work in people with less severe disorders with relatively normal cognitive functioning. Methods: This secondary analysis evaluated cognitive predictors of work in Social Security Disability Insurance (SSDI) beneficiaries with a recent work history who were randomized to receive mental health services, supported employment, and freedom from work disincentives over a 2-year study period in the Mental Health Treatment Study. Of the 1045 participants randomized to the treatment package, 945 (90.4%) received a cognitive assessment at study entry. Competitive work activity was evaluated using a computer-assisted timeline follow-back calendar at baseline and quarterly for 24 months. Results: Mood disorders were the most common psychiatric diagnoses (64.9%), followed by schizophrenia or schizoaffective disorder (35.1%). Tobit regression analyses predicting the average number of hours worked per week, controlling for demographic characteristics, diagnosis, and work history indicated that the cognitive composite score ( P < .01) and verbal learning subscale scores ( P < .001) were associated with fewer hours of weekly work over the study period. Conclusions: Cognitive functioning predicted work over 2 years in SSDI beneficiaries with mood or schizophrenia-spectrum disorders who were receiving supported employment and mental health interventions, despite a relative absence of cognitive impairment in the study participants. The findings suggest cognitive functioning contributes to competitive work outcomes in persons with psychiatric disorders who have relatively unimpaired cognitive abilities, even under optimal conditions of treatment and vocational support.